2004
DOI: 10.1111/j.1468-0343.2004.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

International Economic Sanctions Against a Dictator

Abstract: Wintrobe's (1990Wintrobe's ( , 1998 dictatorship model is adapted to examine the impacts of economic sanctions on an autocrat. It is shown that the dictator's choice of the level of power, and the quantities of loyalty and repression used as inputs in the production of power, are affected by the type and magnitude of sanctions and by the impact of sanctions on the political effectiveness of opposition groups. Sanctions have direct and indirect effects on the prices of loyalty and repression as well as potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 22 publications
(20 reference statements)
1
68
0
1
Order By: Relevance
“…Evenett (2002) estimates the impact of eight industrialized countries' sanctions against 1 There are also theoretical public choice and game-theoretical analyses on conditions under which economic sanctions may trigger policy changes. Examples are Kaempfer et al (2004), Lowenberg (1988, 1999), and Eaton and Engers (1992).…”
Section: Introductionmentioning
confidence: 99%
“…Evenett (2002) estimates the impact of eight industrialized countries' sanctions against 1 There are also theoretical public choice and game-theoretical analyses on conditions under which economic sanctions may trigger policy changes. Examples are Kaempfer et al (2004), Lowenberg (1988, 1999), and Eaton and Engers (1992).…”
Section: Introductionmentioning
confidence: 99%
“…To summarize, single-party and military regimes conform well to the strategic responses set out by Gershenson and Grossman (2001) and, in some way, to the second case dealt with by Kaempfer, Lowenberg and Mertens (2004), in which sanctions have little effect on the opposition's strength. Under both approaches, cooptation and repression should both be increased, as rulers in these regime types seem effectively to do.…”
Section: Figure 1 Revenue Composition (As a % Of Gdp) Aid Per Capitmentioning
confidence: 56%
“…In fact, it has already been shown that authoritarian regime types mediate the impact of variables such as growth and contentious collective action on the likelihood of regime breakdown (Geddes 2004;Ulfelder 2005). The argument about rent creation and appropriation in the event of sanctions has been developed by Kaempfer, Lowenberg and Mertens (2004), who, departing from Wintrobe's (1998) well-known model, assume that sanctions make the size of the dictator's budget grow − as he is able to capture the rents associated with trade restrictions − and hence focus on the effect of sanctions on the level of opposition to the regime. According to them, if sanctions increase the capacity of the opposition, then they may reduce the budget of the dictator and increase the price of repression.…”
Section: Sanctions Patronage and Repressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant focus on the financial impact of sanctions (for example, see Hufbauer et al 2007;Jing et al 2003;Kaempfer and Lowenberg 1999;Kaempfer et al 2004) has obscured the possibility that a state "may initiate sanctions not simply to compel action on the part of the target, but to communicate its preference, support allies, deter others from engaging in similar activity, and dissuade the target from expanding its objectionable activity" (Kirshner 1997: 34). Thus, sanctions not only coerce regimes into compliance or constrain them, but also send signals (Giumelli 2010(Giumelli , 2011) that profoundly affect domestic political struggles, particularly how the regime in power and its opponents position themselves vis-à-vis each other and the external coercion.…”
Section: Resultsmentioning
confidence: 99%